The development of psilocybin therapy for treatment-resistant depression: an update - Anya Borissova; James J. Rucker (BJPsych Bulletin, 2024)
Psilocybin is a classic psychedelic drug that has attracted increasing research interest over the past 10 years as a possible treatment for mood, anxiety and related conditions. Initial phase 2 clinical trials of psilocybin given alongside psychological support for major depression and treatment-resistant depression (TRD) demonstrated encouraging signs of basic safety, further confirmed by a large study in groups of healthy volunteers. The first international multi-centre randomised controlled trial was published in 2022, with signs of efficacy for the 25 mg dose condition in people with TRD when compared with an active placebo. Phase 3 trials in TRD are scheduled to start in 2023. Early evidence suggests that single doses of psilocybin given with psychological support induce rapid improvement in depressive symptoms that endure for some weeks. We therefore provide a timely update to psychiatrists on what psilocybin therapy is, what it is not, and the current state of the evidence-base.